High-Energy Emission and Absorption in Cygnus X-1 - del Valle, Maria Victoria (2010)
The high-mass microquasar Cygnus X-1 has been detected during a flaring state at very high energies, E > 200 GeV. The observation was performed by the Atmospheric Cherenkov Telescope MAGIC. It constitutes the first experimental evidence of very-high energy (VHE) emission produced by a Galactic stellar-mass black hole. The observed signal was detected in coincidence with an X-ray flare. The gamma-ray flare occurred when the compact object was located behind the companion star with respect to the line of sight (superior conjunction of the compact object). In this configuration the absorption of VHE photons by annihilation with the stellar photons is expected to be maximum. This suggests that the emission has been originated far above the compact object. The energy spectrum is well fitted by a relatively soft power-law. We present a model for the absorption and the emission of VHE gamma-rays in Cyg X-1. Detailed calculations of the gamma-ray opacity due to pair creation are provided and used to establish constraints on the emitting region. We propose that the high energy flare was the result of the interaction between the jet and a very dense clump from the stellar wind.